Nazwy zawodów oraz stanowisk świeckich i kościelnych w toponimach dzierżawczych na dawnych Kresach południowo-wschodnich w wiekach XVI-XIX - Pluskota, Teresa (Acta Polono-Ruthenica, 2018)
Multiculturalism of the former south-east borderlands is also reflected the local nomenclature which is often geographically diverse. Possessive names with suffixes -ov, -in, especially with -(ov)ka form a significant group of toponyms which have emerged over the centuries. -ovka affix was productive in the seventeenth and eighteenth century. It created a lot of new names of places, still new language versions of professions emerged, such as Polish bednarz, tokarz et al. Among profession-derived toponyms there are many place names in which we can just clearly determine Ukrainian and Polish stems, conf. Popowka, Xiędzówka, and those in which such differentiation is not so clear, e.g. Kowalowka. The paper shows both the groups. The assumed research period (16th-19th c.) allows in turn to show some changes in a given group of toponyms such as the emergence of variants of Polish names which fall within the toponymy as the Polish influences were broadening eastwards and polonisation was progressing in the 17th and 18th century.